The influence of servicescape upon retailers on customer value in Malaysia / Baderisang Mohamed and Aliaa Adriana Mohd Damanhuri - Mohamed, Baderisang; Mohd Damanhuri, Aliaa Adriana (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Malaysia is experiencing exponential growth in retail sector especially in urban area. Due to this reason a lot of investments are happening in Malaysia and new markets are entering this sector. Many retailers assume that service environment is not an important tool in marketing industry. In today’s marketing strategy, market-oriented businesses in particular, continue to build and match demand with the needs of the target market. The study aims is to analyze the influential factor of servicescape upon retailers on customer value in Malaysia. It is understood that the service environment or servicescape in which service is offered has a great impact on the desired customer experiences and their satisfaction. Study revealed that emotional and novelty values are relevant in retailer’s context.